Psychiatric nursing and mental health teaching in relation to Brazilian curriculum - Camila Ester Fuentes Olmos; Jeferson Rodrigues; Monica Motta Lino; Murielk Motta Lino; Josicélia Dumêt Fernandes; Daniele Delacanal Lazzari
ABSTRACT Objectives: to know the scientific production on psychiatric nursing and mental health teaching in relation to Brazilian nursing curriculum. Methods: an Integrative Literature Review with no temporal delineation, whose data collection took place in ten Brazilian and international databases, adding to the total 35 objects of analysis. Results: a priori categories were adopted, consisting of the psychiatric nursing and mental health teaching in Brazil according to the 1923, 1949, 1962, 1972, 1994 and 2001 nursing curriculum, presented in the light of the dimensions: thought model; places of practice; methods or contents used; and profile or skills of the student. Final considerations: the study made it possible to observe psychiatric nursing and mental health teaching historical evolution, indicating that teaching transformations involved changes in curriculum, Psychiatric Reform and the way nursing undergraduate courses and schools take these determinants.